Being Indian, being MK: an exploration of the experiences and ethnic identities of Indian South African Umkhonto we Sizwe members - Lalla, Varsha (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2011)
Umkhonto we Sizwe (MK) was a military organization dominated by black Africans. Although it is not generally associated with Indian South Africans, who form a minority in the country, there were Indian MK members. This thesis explores the way in which Indian MK members reconciled aspects of their ethnic identity with their membership of MK. It explores the experiences of two generations of members: those born between 1929 and 1944 and those born between 1960 and 1969. In particular it looks at whether they experienced tensions between their ethnic and political identities. It explores what set these Indian South Africans apart from the rest of the Indian South African community that did not join MK. It also looks at what significant differences there were between different generations of Indian MK members. The research results show that the first generation MK members believe that their MK activities were the highest form of passive resistance"Ÿ. An explanation for this way of referring to their activities could be that this was a way of reconciling tensions between their ethnic and political identities. The first generation was also very critical of the Indian SA community. This could be because they still feel part of this community despite having a strong political consciousness that is different from most of the community. It was found that some of the features that set Indian MK members apart from other Indian South Africans were that they were not raised in very religious households and occupied a fairly low rather than middle man"Ÿ economic position. In addition, members of the first generation of MK members were raised in comparatively multi-racial areas. Both generations made the decision to join MK because of Indian role models. There were some marked differences between the two generations of MK veterans. Most notably, the younger did not see their activities as in line with passive resistance and they also displayed more ambivalence about their ethnic identities.
Keywords: Umkhonto we Sizwe (South Africa) -- Research|Political activists -- Research -- South Africa|East Indians -- Politics and government -- Research -- South Africa|Ethnicity -- Political aspects -- South Africa -- Research